Controlled trial of rifampicin and ethambutol in Crohn's disease. Issue 2 (February 1984) - Shaffer, J L; Hughes, S; Linaker, B D; Baker, R D; Turnberg, L A
Abstract : We pursued the possibility that Mycobacterium kansasii might be an aetiological agent in Crohn's disease by carrying out a trial of treatment with antimycobacterial drugs. Twenty seven patients with Crohn's disease took part in a two year randomised double blind, crossover, controlled trial of rifampicin plus ethambutol against placebo. Fourteen patients completed the trial; four required an operation; five were withdrawn as poor compliers, and four because of adverse effects. There was no significant difference in response to the active drugs compared with placebo when expressed in terms of a Crohn's disease activity index or any clinical indicator of disease activity. There was no suggestion that any subgroup of patients - for example, different regions of bowel affected or previous operation - were favourably affected by the drugs. There was no consistent pattern of change in prednisolone requirements although eight patients on long term sulphasalazine had a significant reduction in their plasma sulphapyridine concentrations during the active treatment period. A significant reduction in total white blood count and an increase in plasma ALT were seen during active therapy. The results of the study do not suggest that rifampicin and ethambutol have a role to play in the treatment of Crohn's disease.